Oblaki in pištole v dramskem opusu Vitomila Zupana - Pezdirc-Bartol, Mateja (Jezik in slovstvo, 2015)
In Slovenian literature studies, Vitomil Zupan is seen as a peculiar author who did not join mainstream literature and whose dramatic oeuvre is characterised as diverse in both form and content. This paper presents the development of Zupan's dramatic work in three phases, emphasising those passages that indicate common thematic and formal principles: his adherence to his own moral philosophy and his efforts to preserve the meaning of the world and the human being; his depiction of acute existential situations in which the dramatic characters have to choose between good and evil; his loosening of traditional dramatic form with leaps across time and space and with a plot that is sometimes fragmented; his faith in language and art, and his associated yearning for understanding. Thus clouds and guns are the motivic fragments that become symbolically decisive and fateful.
Keywords: Zupan, Vitomil, 1914-1987; slovenski dramatiki; slovenska književnost; Slovene literature; slovenska dramatika; motivi; teme; dramska oblika